Model Grand Theory Tata Kelola Organisasi Pendidikan Islam Berbasis Kepemimpinan Spiritual dan Teknologi : Penelitian - Yuli Supodo; Patria Yunita (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aimed to develop a grand theory model of Islamic education organization governance based on spiritual leadership and digital technology to address 52% HRM disparities and low AI adaptation in Islamic educational institutions. A qualitative descriptive approach was employed through classical library studies (Al-Mawardi, Ibn Khaldun), semi-structured interviews with 10 MPI experts, and NVivo thematic analysis of 25 governance-related Quranic verses. The research produced an interconnected four-pillar model taqwa-digital structure (82% effectiveness), amanah-AI culture (65%), QS. Al-Hasyr:18 reflective performance evaluation (78%), and contingency leadership (85%) with 85% organizational resilience index and inter-pillar correlation r=0.78. The model proved holistic in synthesizing classical spiritual values with AI ethics infrastructure, providing theoretical and practical contributions through taqwa monitoring dashboard for contemporary Islamic education governance transformation.